Exploring the user experience (UX) of a multi-window augmented reality environment - Sinlapanuntakul, Pitch; Korentsides, Jenna; Chaparro, Barbara S. (Frontiers in Virtual Reality, 2023)
Augmented reality is an emergent form of technology that allows users to interact with and manipulate virtual objects and information integrated into the physical environment. Whether it is replying to browser-based emails or playing a game, completing such tasks in augmented reality requires the use of hand-tracking gestures or interactions. With the anticipated growth of this technology, future users may experience it for extended periods with a variety of applications (e.g., metaverse). This study explores the perceptions and user experience of individuals when interacting with and maneuvering in a multi-window augmented reality environment, using a range of handtracking interactions. The results provide both qualitative and quantitative insights into these interactions, highlighting the impact of perceived usability, subjective user experience, perceived difficulty, and perceived workload on task completion.